The Relationship Between Emotional Intelligence and The Performance of Nurses in Medan Private Hospital - Gurning, Yanty; Siregar, Wiyanna Mathofani (Jurnal Keperawatan Priority, 2024)
Nurse performance is the result of nursing services, which determines the quality of health services and factors determining the image of health services institutions in the eyes of the community and demonstrate service. This study aims to analyze the relationship between nurses’ emotional intelligence and the performance of implementing nurses. The research design used was an analytical survey with a cross-sectional approach. The sample consisted of 114 people. Data collection tools using questionnaires and observation sheets were then analyzed using the Chi-Square statistical test with a confidence level of 95%. The results of the study showed that the emotional intelligence of nurses obtained a p-value of 0,001 < α = 0,05. So, there is a positive relationship between emotional intelligence and the performance of executive nurses in Medan Private Hospital. In conclusion, emotional intelligence is closely related to the performance of implementing nurses.